Pengembangan Ekowisata Mangrove berbasis Masyarakat Desa Batu Ampar Kabupaten Anambas - Abd Qodir Jailani; Hambali Hambali; Firkawin Zuska (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
Anambas Islands tourism is supported by most of the natural potential that has selling power to tourists, one of which is mangrove ecotourism. This study will discuss the development of community-based mangrove ecotourism by looking at the community's perspective in planning, implementing, and managing ecotourism. The research was conducted using descriptive qualitative methods and participatory observation in Batu Ampar Village to be able to describe or explain clearly what facts are in the field. The data were analyzed descriptively and then the SWOT analysis was used to analyze the management strategy in developing mangrove tourism areas based on the community's perspective. The results of the study show that the community already has its own plans for the development of mangrove ecotourism based on existing local knowledge and the entire community is ready to support future development, and is open to tourists who want to visit. With the presence of mangrove ecotourism in Batu Ampar Village, the community hopes to open new jobs and develop existing UMKM. However, from the tourism manager, there are still many things that must be developed in the mangrove ecotourism of Batu Ampar Village to make it a sustainable tourism object.